Epidemiological profile of malignant neoplasms of the prostate in Brazil - Description of half a decade and the influence of the SARS-CoV-2 pandemic (Research, Society and Development, 2024)
Prostate cancer (PC) is the 2nd most common in men. When compared with other malignancies, regional and ethnic disparities remain a problem. Screening is carried out through prostate specific antigen (PSA) measurement and digital rectal exam, and, if necessary, biopsy. There is controversy regarding the benefit of annual screening. Given the importance of epidemiological studies, this study aimed to quantify reported cases and describe factors related to the mortality rate and number of hospitalizations for PC between the years 2018 and 2023. The data were obtained from the SUS Information Technology Department (DATASUS), ICD10-C61 (malignant neoplasm of the prostate) by place of residence. The population studied are men aged 40 or over. Epidemiology in Brazil is like developed countries, despite regional disparities. More hospitalizations occurred in the Southeast and fewer in the North, along with the highest mortality rate. Inequalities between Regions are due to unequal access by the State. There is a predominance in the mortality rate at 80 years of age or more and a greater number of hospitalizations at 60 to 69 years of age. Mixed race people had a higher number of hospitalizations. The highest mortality rate occurred in 2021 and the highest number of hospitalizations in 2022 and 2023, which may be influenced by the SARS-CoV-2 pandemic. Analyzing the profile of this neoplasm is essential to guide the planning of public policies, requiring measures to provide more equitable access to health facilities.